Closing the Mentorship Gap: Implementation of Speed Mentoring Events for Women Faculty and Trainees in Anesthesiology - E. Morgan Pollard; Emily E. Sharpe; Bhargavi Gali; Susan M. Moeschler (Mary Ann Liebert, 2021)
Introduction: Mentorship is a key component to success in academic medicine. Women are under-represented in leadership positions within medicine. Women are less likely to identify mentors than men. Speed mentoring is an innovative strategy to facilitate mentorship in academic medicine. Materials and Methods: A speed mentoring event for women faculty members in an academic anesthesiology department was held, followed by a second event for trainees. Attendees completed surveys about mentorship experiences at baseline and in follow-up. Questions were rated on a 7-point Likert scale with 1?=?strongly disagree and 7?=?strongly agree with values reported as median (1st, 3rd quartile). Results: Baseline surveys indicated poor satisfaction with mentoring in the prior 6 months as 4.5 (3, 5.25). Twelve months later, mentees reported increased satisfaction with mentoring 6 (6, 6). Mentors and mentees felt their time was well spent during both events. There was an increase in the number of mentors identified after the events by both groups. Conclusions: Our results suggest speed mentoring is well received and impactful with minimal time and monetary investment. The attendees of the events identified an increased number of mentors after speed mentoring events, and this effect was maintained at 6?12 months. Speed mentoring may be one path to providing support for women to advance their careers in academic medicine. More research is warranted to better evaluate effectiveness of formats such as speed mentoring to facilitate improved mentorship for women in academic anesthesiology.